2022
DOI: 10.1002/elsc.202100106
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of bio‐separation and bioanalysis using synthetic polymers: Molecularly imprinted polymers (MIPs), cryogels, stimuli‐responsive polymers

Abstract: Bio-separation plays a crucial role in many areas. Different polymers are suitable for bio-separation and are useful for applications in applications in both science and technology. Besides biopolymers, there are a broad spectrum of synthetic polymers with tailor-made properties. The synthetic polymers are characterized by their charges, solubility, hydrophilicity/hydrophobicity, sensitivity to environmental conditions and stability. Furthermore, ongoing developments are of great interest on biodegradable poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 86 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…It was reported that the M13 phage has a length of about 930 nm and a width of about 6 nm, 31 which was much smaller than the pore size of the cryogels, so it could be facilitated the binding of the phages to the cryogels and the passage of the phages through the cryogels. Moreover, cryogels with properties such as elasticity, chemical stability, and biocompatibility could make it widely used for chromatographic elution of biological particles 32 . In addition, AGE was used to insert reactive epoxy groups on the surface of frozen gels for coupling EDA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the M13 phage has a length of about 930 nm and a width of about 6 nm, 31 which was much smaller than the pore size of the cryogels, so it could be facilitated the binding of the phages to the cryogels and the passage of the phages through the cryogels. Moreover, cryogels with properties such as elasticity, chemical stability, and biocompatibility could make it widely used for chromatographic elution of biological particles 32 . In addition, AGE was used to insert reactive epoxy groups on the surface of frozen gels for coupling EDA.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cryogels with properties such as elasticity, chemical stability, and biocompatibility could make it widely used for chromatographic elution of biological particles. 32 In addition, AGE was used to insert reactive epoxy groups on the surface of frozen gels for coupling EDA.…”
Section: Preparation Of Cryogelsmentioning
confidence: 99%
“…Moreover, cryogels had properties such as elasticity, chemical stability and biocompatibility and were therefore widely used for chromatographic elution of biological particles. [32] In addition, AGE was used to insert reactive epoxy groups on the surface of frozen gels for coupling EDA.…”
Section: Preparation Of Cryogelsmentioning
confidence: 99%
“…MIPs are considered interesting candidates owing to their prominent privileges, such as reversible binding capacity, great specificity, and applicability in harsh environments. [ 17 ] In addition, magnetic nanoparticles have attracted a great deal of interest due to their great potential application in enzyme immobilization, [ 18 ] bio‐separation, [ 19 ] targeted drug delivery, [ 20 ] and biosensors. [ 21 ] Recently, there has been substantial research on magnetic molecularly imprinted polymers (MMIPs) for selective recognition and removal of targets from the complex matrix.…”
Section: Introductionmentioning
confidence: 99%